2007
DOI: 10.1159/000112793
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Conventional Transbronchial Needle Aspiration in Pulmonologists Experienced in Bronchoscopy

Abstract: Background: Despite its proven efficacy, transbronchial needle aspiration (TBNA) remains an underutilized technique for sampling enlarged mediastinal lymph nodes in the staging of lung cancer. Previous investigators have reported on TBNA experience, but without mentioning individual learning curves related to lymph node size in pulmonologists experienced in bronchoscopy. Objectives: The aim of this study was to evaluate the TBNA learning curve in a group of pulmonologists already experienced in bronchoscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Therefore, current guidelines describe that NSCLC patients with suspected LN involvement should undergo tissue sampling for pathological confirmation before surgical interventions [1,2,3]. For this aim, transbronchial needle aspiration (TBNA) has been sometimes attempted, but the procedure is not easy and the diagnostic yield is not sufficient [28,29]. Recent surgical and mediastinoscopic techniques for N-staging, such as transcervical extended mediastinal lymphadenectomy (TEMLA) and video-assisted mediastinoscopic lymphadenectomy (VAMLA), have become more accurate [30,31], but these procedures are still invasive, costly and require general anesthesia, as well as a long time and substantial manpower.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, current guidelines describe that NSCLC patients with suspected LN involvement should undergo tissue sampling for pathological confirmation before surgical interventions [1,2,3]. For this aim, transbronchial needle aspiration (TBNA) has been sometimes attempted, but the procedure is not easy and the diagnostic yield is not sufficient [28,29]. Recent surgical and mediastinoscopic techniques for N-staging, such as transcervical extended mediastinal lymphadenectomy (TEMLA) and video-assisted mediastinoscopic lymphadenectomy (VAMLA), have become more accurate [30,31], but these procedures are still invasive, costly and require general anesthesia, as well as a long time and substantial manpower.…”
Section: Discussionmentioning
confidence: 99%
“…However, TBNA of a mediastinal lymph node can be successfully performed by every bronchoscopist. Hermens et al [27] showed in a small group of pulmonologists already experienced in bronchoscopy that the diagnostic yield of TBNA in mediastinal lymph nodes was related to lymph node size, but not to lymph node location and bronchoscopist experience with TBNA. In our study, TBNA was the most frequently performed diagnostic procedure in 59% of patients without any associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of on-site evaluation is advocated for the determination of material adequacy, reduction of nondiagnostic rate, and preliminary diagnoses. [20][21][22][23][24][25] Some authors have also reported that appropriate training can dramatically increase the performance of onsite evaluation. 26 In addition, on-site evaluation allows for proper triaging of specimens, requesting further sampling when additional specimen is needed for ancillary studies, such as cell block, flow cytometry, and microbiology culture.…”
Section: Adenocarcinoma (Nos¼1) Suspicious For Bac (N¼1)mentioning
confidence: 99%